An efficient and facile ring closure of 2’-hydroxychalcones under irradiation of tungsten light - Zangade, Sainath; Shinde, Avinash; Patil, Arvind; Vibhute, Yeshwant (European Journal of Chemistry, 2012)
An efficient, green and facile reaction has been reported between 2’-hydroxychalcones and hydrazine hydrate in 2-methoxyethanol in presence of catalytic amount of acetic acid under irradiation of tungsten light to afford 2-pyrazolines. Present methodology presents several advantages including simple reaction procedure, no need of catalyst/special apparatus and short reaction time giving quantitative yields of product.